(untitled) (Research, Society and Development, 2020)
University sports have been held in Brazil since the beginning of the 19th century and currently occurs in two formats, the official with the organization by consolidated and representative entities, and the other with autonomous organizations, organized and developed through students. This article aims to describe the institutionalization process and the subsequent development of university sports in Brazil and in Brazilian universities, highlighting its historical path and its current reality. The study is characterized as qualitative of a descriptive nature, as it sought to analyze the development of Brazilian university sports and present its current reality. As a result, we highlight that the two competition formats present the sports dispute system, using the same guiding rules of the sports modalities in common, however they differ in their intentionality. In official competitions, there is a search for national representation through the results achieved. In events organized by academics, socialization and other parallel competitions allow academics to compete in addition to sports.